The Effect Of Institutional Ownership, Proportion Of Independent Board Of Commissioners, And Sustainability Committee On Green Banking Disclosure - Willy Sri Yuliandhari; Ajeng Luthfiyatul Farida; Dirrie Nabhila Ginting (SEIKO : Journal of Management & Business, 2021)
Abstract The purpose of this study was to determine the simultaneous and partial effect of institutional ownership, the proportion of independent board of commissioners, and the sustainability committee on green banking disclosure. The methods of this article are quantitative. The population, in this case, is conventional commercial banking was listed on the Indonesia Stock Exchange in 2018-2021. This study use the Purposive sampling technique and obtained observational data from as much as 40 observations consisting of 10 samples of conventional commercial banking with a research period of four years. This study uses panel data regression analysis with the selected model the fixed effect model. The results of this study indicate that the variables of institutional ownership, the proportion of independent board of commissioners, and the sustainability committee simultaneously affect the variable of green banking disclosure in conventional commercial banking. Partially, institutional ownership and the proportion of independent board of commissioners do not affect green banking disclosure, while the sustainability committee has a positive effect on green banking disclosure. The author suggests furthering researchers to use other variables that have a possible effect on green banking disclosure. Keywords: Institutional ownership, independent board commissioners, sustainability committee, green banking disclosure